Genetic organization and regulation of proteins associated with production of syringotoxin by Pseudomonas syringae pv. syringae. - Morgan, M K (1988)
Many strains of Pseudomonas syringae pv. syringae produce one of two low-molecular-weight, peptide-containing phytotoxins, either syringomycin (SR) or syringotoxin (ST). An analysis of Tn5-induced ST-mutants revealed alterations in the presence of two large proteins (ca. 470 and 435 kilodaltons). Apparent truncated forms of the 470 (ST1)- or 435 (ST2)-kilodalton proteins were observed in some mutants. Mapping of the Tn5 insertions and size determinations of truncated proteins suggested that both ST1 and ST2 are in the same transcriptional unit, with ST1 being directly upstream of ST2. When an ST-producing strain of P. syringae pv. syringae was grown under toxin-inducing conditions, ST1 and ST2 were first detected at the end of the exponential phase of growth, which was when the first accumulation of ST was observed. High iron levels were essential for efficient ST production. At concentrations of FeCl3 of between 0.2 and 5 microM, the amount of toxin accumulated was almost directly proportional to the iron concentrations. The amount of ST1 and ST2 present showed a corresponding increase in response to iron concentrations. Our genetic and physiological data implicate ST1 and ST2 in the biosynthesis of syringotoxin.